Czasopismo "Kino" jako popularnonaukowe źródło wiedzy o filmie w Polsce = "Kino" magazine as a non-specialized source of knowledge about films in Poland - Domke, Radosław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article focuses on the history of "Kino" monthly magazine. This periodical has been published continuously since 1966, at the beginning as a black and white periodical, and with time as a colorful and larger volume. It presents information about the life of movie stars, the premieres of new productions and numerous cross-sectional texts on the cinema. A historian can find many articles in it, which, in a synthetic way, try to capture contemporary films as the source for depicting the society.
Keywords: Kino (czasopismo); czasopismo filmowe; miesięcznik; kultura i sztuka; Kino (magazine); monthly; culture and art; film magazine